Evaluating Risk in Business Ethics Case Studies - Maundrell, R. (Teaching business ethics, 2003)
Business management often involves decisionsabout risks to human health and such cases tendto be central to business ethics courses. Overthe last two decades much development has takenplace in the science of risk analysis andlessons have emerged from this work which willmake a useful addition to the ethicalevaluation of case study material in a businessethics courses., In particular, students need to be familiarisedwith and made cautious of the notion ofacceptable risk.